Parent entity and creditor pressure on corporate earnings management: Evidence from listed companies in Southeast Asia - Budiman, Ahmad; Putranti, Eti; Kusuma, Marhaendra (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study investigates the moderating effect of non-controlling interests in subsidiaries (NCIS) on the influence of pressure from parent entity shareholders (PES) and creditors on corporate earnings management (CEM).Design/Methodology/Approach: Data from 3,882 firm-years from companies listed on the largest capital markets in five Southeast Asian countries from 2019 to 2024 were used. Moderated regression analysis was used.Research findings: Pressure from PES and creditors has a positive effect on CEM, and the presence of NCIS weakens this effect.Theoretical contribution/Originality: This study aligns with agency theory, stating that agency problems arise between management, PES, NCIS, and creditors. This study also aligns with fraud theory, stating that pressure from PES and creditors stimulates CEM, and the presence of NCIS reduces management's opportunity to engage in CEM practices. This study extends the previous earnings management literature by isolating the pressure exerted solely by parent-entity shareholders and empirically testing the moderating role of non-controlling interests.Practitioner/Policy implication: NCIS can monitor management performance and intervene with PES and creditors. Although NCIS lacks control and holds a small number of shares, annual shareholder meetings and its representation on the board of commissioners serve as a means for NCIS to exercise its oversight function, including the board of directors' actions to implement CEM.Research limitation/Implication: This study uses three dimensions of the fraud triangle to identify the determinants of CEM actions and examine the moderating role of NCIS. It does not include other factors influencing CEM, as fraud theory has evolved, reaching the hexagon of fraud theory, or perhaps even more than seven dimensions.